Chemical risk and safety awareness, perception, and practices among research laboratories workers in Italy - Papadopoli, Rosa; Nobile, Carmelo Giuseppe Angelo; Trovato, Alessandro; Pileggi, Claudia; Pavia, Maria (Journal of occupational medicine and toxicology (London, England), 2020)
Exposure to chemical compounds occur in numerous occupational settings, among which the research and healthcare laboratories have not been adequately investigated. These settings are characterized by an extreme variability of the used compounds and by the frequent turnover of young researchers. The main objectives of the study were to explore the occupational exposure to hazardous chemical substances among research laboratory workers; to assess their awareness and perceptions regarding chemical hazards; to investigate adherence to guidelines on safe handling of chemical compounds; and to analyze the effects of several factors on these outcomes of interest. The survey was conducted among research laboratories workers who were exposed to chemical substances during their activity. Subjects completed a questionnaire exploring knowledge, attitudes and behaviors related to chemical hazards involved in research activities. Enrolled subjects were 237, for an 81.7% response rate. More than 90 hazardous chemical substances were used in the surveyed laboratories. A correct knowledge on hazardous chemicals was significantly more likely in younger researchers, in those manipulating a higher number of hazardous chemicals, and in those with a higher number of years of training in the attended laboratory; 54.4% of the workers said they felt very exposed to chemical risk. Correct practices in the laboratories were significantly more likely in researchers who perceived to have a low exposure to chemicals, but a high exposure to biological risk, who agreed with the statement that colleagues handle chemicals following safety procedures and who perceived to have received an adequate training in the management of accidents and first aid. Our results showed significant gaps in knowledge and scarce preparedness in the adherence to safety processes to prevent and contain risks related to use of chemical compounds in research laboratories.